Fixed scattering section length with variable scattering section dispersion based optical fibers for polarization mode dispersion penalties - Mahmoud M. A. Eid; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
This study has clarified the fixed scattering section length with variable scattering section dispersion based optical fibers for polarization mode dispersion penalties at high data rates. The max. signal power/min. noise power is simulated against time after fiber length of 500 km with various scattering section dispersion. The overall total light power is simulated after fiber length of 500 km with various scattering section dispersion. In addition to the overall total electrical power is clarified through APD receiver at fiber length of 500 km with various scattering section dispersion. Eye diagram analyzer for signal quality is also simulated through APD receiver at fiber length of 500 km with various scattering section dispersion. The max. Q Factor, electrical signal power after APD receiver variations against scattering section dispersion variations for various data rates.